Implementación de un sistema de control interno bajo la metodología del coso III para “Servyacon Ferretería” ubicada en la provincia de Cotopaxi, cantón Latacunga - Caguano Yugsi, Johana Maribel (2015)
“SERVYACON hardware” store is an entity directed to trade building material, that main detected lack is, low policies, function manuals and some procedures that let to promote effectiveness on its comercial activities getting true and timely information on making decisions of the company. To do the present research interviews and quizzes were applied over administrative, financial, and operational company’s staff through it could determine needs which ones presented the necessity to implementan Internal System Control under COSO III methodology. About Enterprise problems, this investigation had as main objective to create control and self-control rules that guarantee acquiring objetives and goals proposed.